A Study of SnnAl Clusters by Density Functional Theory: Comparison with Their Anions and Cations. Issue 12 (22nd August 2019) - Shi, Shunping; Deng, Banglin; Liu, Yiliang; He, Jiuning; Li, Xia; Jiang, Gang; Li, Yong
Abstract : The atomic structures, stabilities, electronic structures, and magnetic moments of neutral and singly positively and negatively charged Sn n Al ( n = 1–10) clusters are calculated with B3LYP/SDD method in density functional theory. Detailed analyses are implemented to acquire the properties of Sn n Al (0, ±1) clusters, such as relative stabilities, electronic properties, natural population analyses, and magnetic moments. The calculation results show that the ground‐state structures of Sn2 Al, Sn7 Al, and Sn8 Al clusters are different from those of Sn3, Sn8, and Sn9 clusters, the variation trend of binding energies of Sn n + 1 and Sn n Al (0, ±1) coincides, and the small kinks are the same. It is found that the changing tendency of the vertical electron detachment energies (VDEs) of Sn n + 1 and Sn n Al (0, ±1) is almost consistent with that of the adiabatic electron affinities (AEAs), except Sn8 Al. Furthermore, the adiabatic ionization potential energies (AIPs) of Sn n Al and Sn n + 1 clusters exhibit oscillatory behavior, but the variation trend of Sn n Al is contrary to that of Sn n + 1 from n = 1 to n = 7. The simulation results indicate that Sn n Al − and Sn n Al + display a similarity in the magnetic moments, when n = 1, 3, 4, 5, 6, 7, and 9. The charges are transferred from Al to Sn in Sn1–4 Al. Abstract : The lowest‐energy structures of Sn n Al clusters are similar to those of Sn n Al ±1 clusters, except Sn6 Al and Sn6 Al ±1, and Sn7 Al and Sn7 Al ±1 . The binding energies exhibit a sequence as Sn n + 1 > Sn n Al − > Sn n Al > Sn n Al +, besides those of Sn7 Al ±1 that present higher stability than Sn7 Al. The HOMO–LUMO gaps of Sn n Al are higher than those of Sn n + 1 .